PENGARUH BUDAYA ORGANISASI DAN KESADARAN KERJA TERHADAP EFEKTIVITAS KERJA PENGAWAI PADA KANTOR DINAS KOMISI PEMILIHAN UMUM (KPU) KABUPATEN PELALAWAN - Permana, Richo Rias; ', Zulfadil; ', Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
awareness by simultaneously and partially to effectiveness of employees in Office Department of National Election Commission (KPU) District Palalawan. The population in this study were all employees of the office inOffice Department Of National Election Commission (KPU) District Palalawan many as 53 people. The sampling is done by making all employees in the sample. Analysis of the data used is descriptive analysis with quantitative analysis tools that multiple linear regression with SPSS version 18:00. Afteranalyzing the data, simultaneous test (F-test) showed that organizational culture and work awareness have significantly influence to effectiveness employees onOffice Department of National Election Commission (KPU) District Palalawan, while the partial test (t-test) organizational culture and work awarenessby partially have significant effect on the effectiveness employees onOffice Department of National Election Commission (KPU) District Palalawan. It is expected that the management of the Office of the General Election Commission (KPU) Pelalawan in order to improve employee satisfaction, for example by providing compensation in accordance with the needs of employees, allowances and other incentives. Thus employees will feel the spirit of the work and effectiveness of employees will also increase. With the implementation of the terms of expected employees will be motivated to achieve corporate goals.Keywords : Organizational Culture, Work Awareness and Effectiveness Employees